Two-dimensional material-based bionano platforms to control mesenchymal stem cell differentiation - Ee-Seul Kang; Da-Seul Kim; Intan Rosalina Suhito; Wanhee Lee; Inbeom Song; Tae-Hyung Kim (Biomaterials Research, 2018)
Abstract Background In the past decade, stem cells, with their ability to differentiate into various types of cells, have been proven to be resourceful in regenerative medicine and tissue engineering. Despite the ability to repair damaged parts of organs and tissues, the use of stem cells still entails several limitations, such as low differentiation efficiency and difficulties in guiding differentiation. To address these limitations, nanotechnology approaches have been recently implemented in stem cell research. It has been discovered that stem cells, in combination with carbon-based functional materials, show enhanced regenerative performances in varying biophysical conditions. In particular, several studies have reported solutions to the conventional quandaries in biomedical engineering, using synergetic effects of nanohybrid materials, as well as further development of technologies to recover from diverse health conditions such as bone fracture and strokes. Main text In this review, we discuss several prior studies regarding the application of various nanomaterials in controlling the behavior of stem cells. We focus on the potential of different types of nanomaterials, such as two-dimensional materials, gold nanoparticles, and three-dimensional nanohybrid composites, to control the differentiation of human mesenchymal stem cells (hMSCs). These materials have been found to affect stem cell functions via the adsorption of growth/differentiation factors on the surfaces of nanomaterials and the activation of signaling pathways that are mostly related to cell adhesion and differentiation (e.g., FAK, Smad, Erk, and Wnt). Conclusion Controlling stem cell differentiation using biophysical factors, especially the use of nanohybrid materials to functionalize underlying substrates wherein the cells attach and grow, is a promising strategy to achieve cells of interest in a highly efficient manner. We hope that this review will facilitate the use of other types of newly discovered and/or synthesized nanomaterials (e.g., metal transition dichalcogenides, non-toxic quantum dots, and metal oxide frameworks) for stem cell-based regenerative therapies.